Attachment and mentalization of teacher as predictors of classroom management style - Nikolić Vesković, Danica (Psihološka istraživanja, 2023)
The aim of this study is to examine whether the tendency towards a certain style of classroom management can be predicted based on the attachment and mentalization of the teacher, as well as whether training in the field of classroom management modifies the relationship between predictor and criterion variables. The research included 100 1st-4th-grade elementary school teachers teachers, 86 female and 14 male, aged from 28 to 64 and with 1 to 39 years of experience. The data were collected with the following instruments: Inventory for self-assessment of teachers' styles in classroom management - ISNUR; questionnaire "Experience in close relationships", Serbian modified and adapted version, SM-ECR-R; Questionnaire for examining the mentalization UM. The results show that anxiety and mentalization of self contribute to the tendency towards the non-intervening and intervening style of classroom management, while the mentalization of others and trainings in the field of classroom management contribute to the tendency towards the interactionist style of classroom management. The moderating effect of training on the relationship between the mentalization of others and the interactionist style of class management was also established.
Keywords: attachment, mentalization, classroom management style, teacher